A novel anti-aging TBS MRPC for CBM-TOF - Yao, Ming; Deppner, Ingo Martin; Wang, K.; Li, W.; Zhou, Y.; Hu, D.; Sun, Y. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
The Compressed Baryonic Matter (CBM) experiment at the Facility for Antiproton and Ion Research (FAIR) aims to investigate the QCD phase diagram in high baryon density regions. Its Time-of-Flight (TOF) system, responsible for hadron identification, uses Multi-gap Resistive Plate Chambers (MRPCs), which are subjected to flux rates as high as 25 kHz/cm2 in specific regions. Under such conditions, traditional MRPCs with fishline spacers show aging effects, including increased dark current, noise, and performance degradation caused by gas ionization and deposit formation near the spacers. This paper introduces a novel MRPC design that employs cylindrical thermal bonding spacers (TBS) instead of fishline spacers to mitigate aging effects. The TBS MRPC was produced and tested under cosmic ray conditions and X-ray irradiation. Comparative testing between the TBS and fishline MRPCs showed a notable reduction in current accumulation and stable noise levels for the TBS design. The detector achieved an efficiency of (97.30 ± 0.20)% and a time resolution of (64.54 ± 0.10) ps, satisfying the requirements of the CBM-TOF system. These results suggest that the TBS MRPC is a suitable candidate for high-rate operation in future CBM experiments.
Online verfügbar: 25. Juni 2025, Artikelversion: 1. Juli 2025
Gesehen am 19.11.2025